PENGARUH PENGETAHUAN KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU MANAJEMEN KEUANGAN(STUDY KASUS PADA MAHASISWA FAKULTAS EKONOMI ANGKATAN 2019) UNIVERSITAS MERDEKA PASURUAN - Agustya Ningsih; Yufenti Oktafiah; Eva Mufidah (Bajang Institute, 2024)
This research is used to find out the influence of financial knowledge and lifestyle on financial management in economics faculty students of the 2019 batch of Universitas Merdeka Pasuruan. The method of sampling in this research is using the Purposive sampling technique with a questionnaire using the Slovin formula with a total of 53 respondents. The analysis used is the Multiple Linear Regression Test. The results of the research show that 1) Financial knowledge, Lifestyle simultaneously has a positive and significant influence on Financial Management Behavior with the value of F count > F table which is 36,560 > 3.18 and sig value. 0.000 < 0.005. 2) Partial financial knowledge has a positive and significant effect on management behavior, ie the value of t count > t table is 2.916 > 2.007 and sig value 0.005 < 0.05. Lifestyle partially has a positive and significant effect on financial management behavior, ie the value of t count > t table is 8.052 > 2.007 and sig value 0.000 < 0.05.